2021
DOI: 10.1021/acs.inorgchem.1c00901
|View full text |Cite
|
Sign up to set email alerts
|

Dimerization-Induced Solid-State Excimer Emission Showing Consecutive Thermochromic Luminescence Based on Acridine-Modified o-Carboranes

Abstract: Although excimer emission is a useful luminescent phenomenon for fabricating optical sensors and probes, it is difficult to apply excimer emission for film sensors due to critical concentration quenching in the solid state. Therefore, robust molecular designs for solid-state excimer emission are still being explored. One of the key examples is the previously reported acridine-ethynyl-o-carborane AcE1, which showed a bright solid-state excimer emission assisted by characteristic CcageH···N interactions. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 53 publications
2
38
1
Order By: Relevance
“…We have previously reported the same results of emission band shifts upon heating. 11,29 From excimer emission, hypsochromic shifts were observed, and it was suggested that intermolecular interaction via p-p stacking should be weakened by the gradual expansion of crystal lattice. In contrast, bathochromic shifts were detected from CT emission and it was proposed that larger structural relaxation could be allowed in weakened crystal packing, where thermal motions at the substituents vigorously occur.…”
Section: Thermochromic Luminescencementioning
confidence: 99%
“…We have previously reported the same results of emission band shifts upon heating. 11,29 From excimer emission, hypsochromic shifts were observed, and it was suggested that intermolecular interaction via p-p stacking should be weakened by the gradual expansion of crystal lattice. In contrast, bathochromic shifts were detected from CT emission and it was proposed that larger structural relaxation could be allowed in weakened crystal packing, where thermal motions at the substituents vigorously occur.…”
Section: Thermochromic Luminescencementioning
confidence: 99%
“…The peak assigned as the C cage À H stretching band shifted to the larger energy region, suggesting the formation of CH•••O interaction. While general hydrogen bonds shift the band to a smaller energy region, [26] the opposite shift is also known as an "improper hydrogen bond," which is sometimes observed in CH•••X hydrogen bonding systems. [31] From these results, the C cage H•••O interaction should be formed both in solution and solid states.…”
Section: Resultsmentioning
confidence: 99%
“…[25] We have recently shed light on this unique interaction to construct solid-state thermochromic materials possessing highly-ordered crystal structures assisted by intermolecular C cage H•••N interactions. [26,27] On the other hand, intramolecular interactions have not been sufficiently investigated except for pioneering works conducted by Endo and co-workers. [28] Those researches focused on 1-(methoxyphenyl)-o-carborane and the intramolecular C cage H•••O interaction was evaluated by NMR spectroscopy and quantum chemical calculations, while optical properties have not been investigated because of its small πconjugation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[47][48][49][50][51][52] Sonogashira coupling of ethynyl boron clusters has only been demonstrated in single reports, and no optimization or generalization of the method have been established. [53][54][55][56] In this study, we report on the Sonogashira coupling of the ethynyl carborane [CB 11 H 11 -12-CCH] − with bromoarenes, affording aryl carboranyl alkynes (Fig. 2c).…”
Section: Introductionmentioning
confidence: 99%